1995
DOI: 10.1093/nar/23.14.2669
|View full text |Cite
|
Sign up to set email alerts
|

U24, a novel intron-encoded small nucleolar RNA with two 12 nt long, phylogenetically conserved complementaritiesm to 28S rRNA

Abstract: Following computer searches of sequence banks, we have positively identified a novel intronic snoRNA, U24, encoded in the ribosomal protein L7a gene in humans and chicken. Like previously reported intronic snoRNAs, U24 is devoid of a 5'-trimethyl-cap. U24 is immunoprecipitated by an antifibrillarin antibody and displays an exclusively nucleolar localization by fluorescence microscopy after in situ hybridization with antisense oligonucleotides. In vertebrates, U24 is a 76 nt long conserved RNA which is metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 47 publications
5
64
0
Order By: Relevance
“…Genetic depletion of Nop58p+ A: Schematic representation of the structure of the GAL::nop58 allele+ B: Growth of the GAL::nop58 (circles) and NOP58 (squares) strains following transfer to glucose medium+ Cell density was measured at regular intervals and the cultures were periodically diluted to be continuously kept in exponential growth+ The results are presented on an exponential scale with the OD values corrected for the dilution factor+ C: Northern hybridization of the NOP58 mRNA in a GAL::nop58 strain+ RNA was extracted from NOP58 and GAL::nop58 strains following growth on permissive rsg medium (0-h lanes) and at intervals following transfer to glucose medium (6-24-h lanes) and separated on a 1+2% agarose gel containing formaldehyde+ ization using specific oligonucleotide probes or antisense RNA transcripts (see Materials and Methods)+ Strong depletion was observed for all tested box CϩD snoRNAs: U3, U14, U18, snR4, snR190 ( Among the box CϩD snoRNAs tested, some variation in sensitivity to the depletion of Nop58p was observed, with higher residual levels of U3 and U24 than other species+ For both of these snoRNAs low levels of longer forms were detected on depletion of Nop58p (Figs+ 4A and 5)+ These extended species were investigated in more detail for U24+ Higher resolution Northerns showed that both shorter and longer forms of U24 were accumulated (Fig+ 5B)+ Primer extension from an internal U24 oligonucleotide revealed that the 59 end of U24 is unaltered in the Nop58p depleted strain (Fig+ 5C)+ RNase protection was used to map the 39 ends of U24 (Fig+ 5D)+ An antisense transcript overlapping the 39 end of U24 was annealed to total RNA+ The RNA hybrids formed were digested with RNase A ϩ T1 and the protected fragments were resolved on a polyacrylamide gel (see Materials and Methods)+ The signal detected in the wild-type NOP58 strain correspond to the position of the authentic 39 end of U24+ In the GAL::nop58 strain, a protected fragment extended by 5 or 6 nt is detected and accumulates over the time course of depletion (Fig+ 5D)+ This would be in good agreement with the gel mobility of the major extended RNA species seen by Northern hybridization+ Why the band corresponding to the size of the mature U24 is not lost from the RNase protection during Nop58p depletion is unclear; we assume this to be an artifact due to the structure of the snoRNA or antisense RNA transcript+ Yeast U24 is encoded in the intron of the BEL1 gene (Qu et al+, 1995) and is produced from the debranched intron-lariat by exonuclease activities (Ooi et al+, 1998; FIGURE 4. The box CϩD snoRNAs are specifically depleted in GAL::nop58 strains+ RNA was extracted from NOP58 and GAL::nop58 strains following growth on permissive rsg medium (0-h lanes) and at intervals following transfer to glucose medium (6-24-h lanes), separated on a 8% polyacrylamide gel and analyzed by Northern hybridization+ A: Probes specific for box CϩD snoRNAs+ B: Probes specific for box HϩACA snoRNAs+ C: Probe to the RNase MRP RNA+ Petfalski et al+, 1998)+ We conclude that depletion of Nop58p interferes with normal 39 processing of U24+…”
Section: Nop58p Is Required For the Stability Of The Box C+d Snornassupporting
confidence: 74%
See 2 more Smart Citations
“…Genetic depletion of Nop58p+ A: Schematic representation of the structure of the GAL::nop58 allele+ B: Growth of the GAL::nop58 (circles) and NOP58 (squares) strains following transfer to glucose medium+ Cell density was measured at regular intervals and the cultures were periodically diluted to be continuously kept in exponential growth+ The results are presented on an exponential scale with the OD values corrected for the dilution factor+ C: Northern hybridization of the NOP58 mRNA in a GAL::nop58 strain+ RNA was extracted from NOP58 and GAL::nop58 strains following growth on permissive rsg medium (0-h lanes) and at intervals following transfer to glucose medium (6-24-h lanes) and separated on a 1+2% agarose gel containing formaldehyde+ ization using specific oligonucleotide probes or antisense RNA transcripts (see Materials and Methods)+ Strong depletion was observed for all tested box CϩD snoRNAs: U3, U14, U18, snR4, snR190 ( Among the box CϩD snoRNAs tested, some variation in sensitivity to the depletion of Nop58p was observed, with higher residual levels of U3 and U24 than other species+ For both of these snoRNAs low levels of longer forms were detected on depletion of Nop58p (Figs+ 4A and 5)+ These extended species were investigated in more detail for U24+ Higher resolution Northerns showed that both shorter and longer forms of U24 were accumulated (Fig+ 5B)+ Primer extension from an internal U24 oligonucleotide revealed that the 59 end of U24 is unaltered in the Nop58p depleted strain (Fig+ 5C)+ RNase protection was used to map the 39 ends of U24 (Fig+ 5D)+ An antisense transcript overlapping the 39 end of U24 was annealed to total RNA+ The RNA hybrids formed were digested with RNase A ϩ T1 and the protected fragments were resolved on a polyacrylamide gel (see Materials and Methods)+ The signal detected in the wild-type NOP58 strain correspond to the position of the authentic 39 end of U24+ In the GAL::nop58 strain, a protected fragment extended by 5 or 6 nt is detected and accumulates over the time course of depletion (Fig+ 5D)+ This would be in good agreement with the gel mobility of the major extended RNA species seen by Northern hybridization+ Why the band corresponding to the size of the mature U24 is not lost from the RNase protection during Nop58p depletion is unclear; we assume this to be an artifact due to the structure of the snoRNA or antisense RNA transcript+ Yeast U24 is encoded in the intron of the BEL1 gene (Qu et al+, 1995) and is produced from the debranched intron-lariat by exonuclease activities (Ooi et al+, 1998; FIGURE 4. The box CϩD snoRNAs are specifically depleted in GAL::nop58 strains+ RNA was extracted from NOP58 and GAL::nop58 strains following growth on permissive rsg medium (0-h lanes) and at intervals following transfer to glucose medium (6-24-h lanes), separated on a 8% polyacrylamide gel and analyzed by Northern hybridization+ A: Probes specific for box CϩD snoRNAs+ B: Probes specific for box HϩACA snoRNAs+ C: Probe to the RNase MRP RNA+ Petfalski et al+, 1998)+ We conclude that depletion of Nop58p interferes with normal 39 processing of U24+…”
Section: Nop58p Is Required For the Stability Of The Box C+d Snornassupporting
confidence: 74%
“…Comparison of different box CϩD snoRNAs revealed some variation in the residual levels on depletion of Nop58p+ For U3, a longer species accumulated, clearly showing an effect on synthesis of the snoRNA+ The 59 end of mature U3 corresponds to the tri-methyl guanosine cap of the primary transcript, and the extended form is therefore very likely to be 39 extended+ In vertebrates and yeast, spliceosomal snRNAs are processed from precursors with 39 extensions (Madore et al+, 1984a(Madore et al+, , 1984bYuo et al+, 1985;Chanfreau et al+, 1997;Abou Elela & Ares, 1998), and U3 may be similarly processed+ Longer forms of U24 were also accumulated, together with low levels of shorter forms+ The 59 end of U24 was unaffected by depletion of Nop58p whereas RNase protection experiments detected species 39 extended by 5-6 nt, showing these changes to be due to alterations in 39 processing+ Yeast U24 is encoded in the intron of the BEL1 gene (Qu et al+, 1995) and the snoRNA is obligatorily synthesized from the intron following debranching of the intron lariat; very low levels of mature U24 are synthesized in a dbr1-⌬ strain that lacks debranching activity (Ooi et al+, 1998;Petfalski et al+, 1998)+ This strongly indicates that both ends of U24 are synthesized by exonucleolytic activities and, indeed, the 59 r 39 exonucleases Rat1p and Xrn1p were identified as the activities responsible for the 59 processing (Petfalski et al+, 1998)+ In vertebrates, the 59 and 39 ends of all tested intronencoded snoRNAs are synthesized by exonucleases (Cecconi et al+, 1995;Kiss & Filipowicz, 1995;Caffarelli et al+, 1996;Xia et al+, 1997)+…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3D and data not shown). In contrast, known ubiquitous intronic C/D box snoRNAs, whether they are encoded in protein genes or in noncoding RNAs, are conserved over a much larger span of vertebrate phylogeny (9,37,39,43,46). The three previously reported brain-specific C/D box snoRNAs also seem substantially more ancient than RBII-36, since their origin must predate the primates/rodents split during mammalian evolution (17).…”
Section: Rat Brain-specific Box C/d Snorna In Repeated Intronsmentioning
confidence: 94%
“…RBII-36 snoRNA Is Only Detected in Rats-Most box C/D snoRNAs have homologues in distant vertebrate species that can be detected by Northern cross-hybridizations using oligonucleotide probes directed to their conserved antisense element (9,43,46). Given that the 3Ј half of RBII-36 snoRNA sequence is preferentially conserved among the different tandemly repeated units (Fig.…”
Section: Rat Brain-specific Box C/d Snorna In Repeated Intronsmentioning
confidence: 99%